PENGUJIAN SYARAT MATERIL SURAT DAKWAAN DALAM PERKARA PERJUDIAN ONLINE (STUDI PUTUSAN PN JAKARTA UTARA NOMOR 43/PID.B 2021): Material Requirement Failures in Online Gambling Indictments: A Case Study of Jakarta Utara District Court Decision No. 43/Pid.B/2021 - Rama Wahyu Pratama Putra; Setiyono (Faculty of Law, Universitas Trisakti, 2025)
The indictment is a legal document submitted by the public prosecutor in criminal proceedings, serving to explain the criminal offense charged against the defendant. The issue examined in this paper focuses on a juridical review of the inaccurate use of an indictment in the North Jakarta District Court Decision Number 43/PID.B/2021/PN JKT.UTR concerning an online gambling offense. This study employs a normative legal research method with a descriptive approach, supported by both primary and secondary legal materials. Data will be collected through literature study and analyzed qualitatively.The discussion and conclusion reveal that although the indictment formally meets the requirements under the Criminal Procedure Code (KUHAP), there is inaccuracy in the selection of the legal basis, which is a material requirement. The public prosecutor charged the defendant under Article 303 of the Indonesian Criminal Code (KUHP), which is more suitable for conventional gambling, whereas the offense committed would be more appropriately charged under Law Number 11 of 2008 on Electronic Information and Transactions (ITE Law). This inaccuracy potentially leads to legal uncertainty in law enforcement and creates juridical consequences for the indictment. This study emphasizes the importance of precision in formulating indictments.